Exploring the World through Social Studies Learning in the Early Grades in a Comprehensive Guide - Rida Nazmi Farhani; Salma Irdhillah; Zidna Syifanadia Impian Pragita; Tin Rustini (COMPETITIVE: Journal of Education, 2025)
Learning Social Sciences (IPS) in the early grades has an important role in opening children's horizons of knowledge about the world around them. Providing an overview of how teachers can create interesting and meaningful social studies learning experiences for early grade students. The aim is to foster children's curiosity and love of the world in an interesting and interactive way, using an experience-based learning approach that allows children to explore various social studies concepts and issues directly, as well as develop critical thinking and problem solving skills through exploration and investigation, and allows them to apply their knowledge in real-world contexts. The method used in this research is a qualitative method with a literature study approach.